2017
DOI: 10.1186/s12906-017-1573-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of some plant materials used in Armenian traditional medicine

Abstract: BackgroundAntibiotic resistance has become one of the major problems facing humanity. The need for new antimicrobials has been increased dramatically. Plants are considered as one of the most promising sources for new antimicrobials discovery. Despite relatively small area, Armenia has large diversity of flora with many endemic species. In Armenian folk medicine plant materials have been used to treat various microbial diseases since ancient times. The goal of our research was to evaluate antimicrobial efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 28 publications
1
89
1
2
Order By: Relevance
“…Five wild Armenian plant materials were collected from Tavush region (1300–1600 m above sea level). The collection, identification and preparation of plant materials were done according to already established protocol (Ginovyan et al ). Identification of plant materials was done at Department of Botany and Mycology, Yerevan State University (Armenia).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five wild Armenian plant materials were collected from Tavush region (1300–1600 m above sea level). The collection, identification and preparation of plant materials were done according to already established protocol (Ginovyan et al ). Identification of plant materials was done at Department of Botany and Mycology, Yerevan State University (Armenia).…”
Section: Methodsmentioning
confidence: 99%
“…Details of tested plant species including their traditional uses and tested parts are presented in Table . The tested plant parts have been chosen based on an initial evaluation of antimicrobial activities of different parts of these plants, as well as their traditional uses (Ginovyan et al ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on plants as a source of treatment for incurable diseases has resulted in a huge demand for medicinal plants. It has been reported that plants have been considered as one of the most sought-after sources for the discovery of antimicrobial agent [12]. The secondary metabolites found in plants are mostly accountable for antimicrobial activity; the major phytoconstituents involved are terpenoids, phenolics, lectins, alkaloids, polyphenols, and polypeptides [13].…”
Section: Introductionmentioning
confidence: 99%